(3GdUMGFa GdEdgjIs - (3GdSeQbfOj , TeS GdOjf eMeO Hf GTQa GdMSjfj GdSeQbfOj,J (B690 (3g` s ((3JHQjR s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ESJMb GdhLhO hGdhMOI HGdPGJ hCHOY dMceJg CfhGY GdeGgjGJ s
(3BNQgG (B:s
(3hbO ChOY ai gPG GdcJGH eG hGdMeO cdg dhGgH GdYbd heajV GdNjQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B63s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs